Piperazine-based N4-type 16-membered macroheterocycles and their nickel(II) complexes - Vatsadze, Sergey Z.; Krut’ko, Dmitry P.; Blake, Alexander J.; Mountford, Philip (ISUCT Publishing, 2017)
Square-planar diamagnetic nickel(II) complexes 5a and 5b containing 16-membered diamino-diimino ligands were prepared from the corresponding open-chain complexes 2a and 2b via condensation with o-phthalic dialdehyde in methanol. The solid-state structure of the starting complex 2b revealed the cisoid conformation of aryl groups compared to the transoid one found in the case of 2a. At the same time, the cisoid conformation is not retained in acetone solution: rather, the tert-Bu-substituted complex 2b was fully transformed into the trans form whereas its analogue 2aexhibits both cis and transforms in acetone solution. The cisoid conformation was also observed for the cyclic structures 5a and 5b by X-ray analysis and VT NMR experiments. The borohydride reduction of 5a with subsequent cyanide-assisted removal of nickel led to a new 16-membered tetraazamacrocycle 6. Its X-ray structure showed a cisoid conformation supported by two intramolecular hydrogen bonds that was also sustained in solution. VT NMR experiments revealed the degenerative interconvertion of a macrocycle with activation energy ca. 41.9±0.8 kJ/mol.